Lovastatin induces G1-phase synchronization of HEC-1-A cells and JEC cells - Huimin Shen; Xiaomao Li; Yuebo Yang; Xiaoyun Wang; Xu Zhang (Bangladesh Pharmacological Society, 2013)
Our study investigated lovastatin-induced G1 phase synchronization of HEC-1-A cells and JEC cells and the cell cycle progression after desynchronization of these cells. HEC-1-A cells and JEC cells were treated with by lovastatin and the proportion of cells in G1 phase was detected. Both cell types were incubated with lovastatin and the synchronization was determined. The cell cycle progression of both cell types was investigated. The proportion of Both cell types in G1 phase was 87.87 ± 0.70% and 85.00 ± 0.79%, respectively. At 20 h and 16 h after G1-phase desynchronization, the proportion of cells in S phase reached a maximal level and that in G1 phase was at the minimal level for HEC-1-A cells and JEC cells, respectively. Thus, at 20 h and 16 h after desynchronization, the proportion of cells in S phase was the highest and that in G1 phase the lowest for HEC-1-A cells and JEC cells, respectively.